Resin composition and molded article
Patent Information
- Application Number
- JP2024068602
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-08-25
- Filing Date
- 2024-04-19
- Publication Date
- 2025-03-07
AI Technical Summary
【0015】 本発明によれば、無機物質粉末を高充填した樹脂成形品における機械的特性のばらつきを抑制する技術が提供される。
Smart Images

Figure 2025031506000001 
Figure 2025031506000002 
Figure 2025031506000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a resin composition and a molded article. [Background technology]
[0002] In recent years, from the viewpoint of reducing the environmental load, attempts have been made to highly fill resin molded articles with inorganic powders (for example, Patent Document 1). Resin molded products highly filled with inorganic powder generally have superior mechanical properties (tensile strength, etc.) compared to resin alone. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2020-158560 A Summary of the Invention [Problem to be solved by the invention]
[0004] However, the present inventors have found that resin molded articles highly filled with inorganic powder tend to exhibit variations in mechanical properties after long-term use, which are thought to be due to resin deterioration.
[0005] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide a technique for suppressing the variation in mechanical properties of a resin molded product highly filled with inorganic substance powder. [Means for solving the problem]
[0006] The present inventors have found that the above problems can be solved by blending an inorganic substance powder that satisfies certain requirements for the content of trace components in a resin molded product highly filled with an inorganic substance powder, and have completed the present invention. More specifically, the present invention provides the following.
[0007] (1) A resin composition comprising a thermoplastic resin and an inorganic substance powder, The content of the inorganic substance powder in the resin composition is 50% by mass or more and 90% by mass or less, the thermoplastic resin includes a polyolefin resin, A resin composition, wherein the inorganic substance powder mainly contains calcium carbonate powder and satisfies all of the following requirements: (Requirement 1) The lead content per gram of the inorganic powder is 19 μg or less. (Requirement 2) When the inorganic substance powder is taken as 100% by mass, the total amount of alkali metal and magnesium is 0.9% by mass or less.
[0008] (2) The resin composition according to (1), wherein the polyolefin-based resin comprises a polypropylene-based resin and / or a polyethylene-based resin.
[0009] (3) The resin composition according to (1), wherein the content of the calcium carbonate powder is 80 mass % or more relative to the inorganic substance powder.
[0010] (4) The resin composition according to (1), wherein the calcium carbonate powder includes ground calcium carbonate powder.
[0011] (5) The resin composition according to (1), in which the inorganic substance powder further satisfies the following requirements: (Requirement 3) The arsenic content per gram of the inorganic substance powder is 3 μg or less.
[0012] (6) The resin composition according to (4), wherein the ground calcium carbonate powder contains ground calcium carbonate powder having an average particle size of 0.7 μm or more and 6.0 μm or less as measured by an air permeation method in accordance with JIS M-8511:2014.
[0013] (7) A molded article containing a thermoplastic resin and an inorganic powder, The content of the inorganic substance powder in the molded article is 50% by mass or more and 90% by mass or less, the thermoplastic resin includes a polyolefin resin, The inorganic substance powder mainly contains calcium carbonate powder, and the molded article satisfies all of the following requirements: (Requirement 1) The lead content per gram of the inorganic powder is 19 μg or less. (Requirement 2) When the inorganic substance powder is taken as 100% by mass, the total amount of alkali metal and magnesium is 0.9% by mass or less.
[0014] (8) The molded article according to (7), which is any one of an injection molded article, an extrusion molded article, an inflation molded article, a vacuum molded article, and a blow molded article. Effect of the Invention
[0015] According to the present invention, a technique is provided for suppressing the variation in mechanical properties of a resin molded product highly filled with inorganic powder. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] Hereinafter, an embodiment of the present invention will be described, but the present invention is not limited thereto.
[0017] <Resin composition> A resin composition according to one embodiment of the present invention contains a thermoplastic resin and an inorganic substance powder including calcium carbonate powder, and has a main technical feature in that the inorganic substance powder satisfies all of the following requirements: (Requirement 1) The lead content per gram of inorganic powder is 19 μg or less. (Requirement 2) When the inorganic substance powder is taken as 100% by mass, the total amount of alkali metals and magnesium is 0.9% by mass or less.
[0018] Inorganic powders (such as calcium carbonate powder) usually contain trace amounts of impurities such as lead and alkali metals. As a result of the investigations conducted by the present inventors, it has been found that such trace impurities are likely to cause variations in the mechanical properties of the resin composition. The effects of such trace impurities can be particularly serious in resin molded products that are highly filled with inorganic powder. Furthermore, the present inventors have found that, among trace impurities, lead, alkali metals, and magnesium in particular are likely to cause variations in mechanical properties, and that the variations can be suppressed by adjusting the content so as to satisfy the above requirements.
[0019] In one embodiment of the present invention, the "mechanical properties of a resin molded product" includes, for example, tensile strength determined by a tensile test in accordance with JIS K7161-1: 2014. Higher tensile strength means better mechanical properties. In a more preferred embodiment of the present invention, the "mechanical properties of a resin molded article" encompasses, for example, the mechanical properties of a resin molded article that has been subjected to a heat aging treatment in accordance with JIS K7368:1999.
[0020] In one embodiment of the present invention, "variation in mechanical properties of a resin molded article is suppressed" means that when a large number of resin molded articles (obtained from a resin composition) are produced under the same conditions, the variation (standard deviation) in mechanical properties among the articles is small (for example, the standard deviation of the mechanical properties is preferably less than 10%, more preferably less than 5%).
[0021] The mechanical properties and variations in the mechanical properties of the resin molded product can be evaluated by the method shown in the examples.
[0022] In one embodiment of the present invention, "consisting of component A" means that the composition is substantially free of components other than component A. In one embodiment of the present invention, "substantially free of component B" includes, for example, an embodiment in which component B is not included at all.
[0023] In one embodiment of the present invention, the phrase "mainly containing component A" means that the content of component A is more than half of the total content of specified components. For example, "mainly comprising component A" encompasses a situation in which the content of component A relative to the total amount of the specified components is preferably 80% by mass or more, more preferably 90% by mass or more, even more preferably 95% by mass or more, even more preferably 99% by mass or more, and most preferably 100% by mass.
[0024] The configuration of a resin composition according to one embodiment of the present invention will be described in detail below.
[0025] (1)Thermoplastic resin The thermoplastic resin is not particularly limited except that it contains a polyolefin resin, and any resin that can be usually blended in a resin molded product can be used. The thermoplastic resin may be used alone or in combination of two or more kinds.
[0026] (1-1) Types of thermoplastic resins The thermoplastic resin includes at least a polyolefin-based resin, and is preferably made of a polyolefin-based resin. Examples of thermoplastic resins other than polyolefin resins include polyester resins and polystyrene resins.
[0027] In one embodiment of the present invention, the term "polyolefin-based resin" refers to a polyolefin-based resin containing an olefin component unit as a main component. "Containing olefin component units as a main component" means that the olefin component units account for 50 mass % or more (preferably 75 mass % or more, more preferably 85 mass % or more, and even more preferably 90 mass % or more) of the polyolefin resin. The method for producing the polyolefin resin used in the present invention is not particularly limited, and may be any method using a Ziegler-Natta catalyst, a metallocene catalyst, a radical initiator (oxygen, peroxide, etc.), or the like.
[0028] Examples of polyolefin resins include polypropylene resins and polyethylene resins. From the viewpoint of easily achieving the effects of the present invention and easily realizing a good appearance, etc., the thermoplastic resin preferably contains a polypropylene-based resin and / or a polyethylene-based resin, and more preferably consists of a polypropylene-based resin and / or a polyethylene-based resin.
[0029] (1-1-1) Polypropylene resin The polypropylene resin in the present invention includes a resin containing propylene component units in an amount of preferably 50% by mass or more, more preferably 60% by mass or more, even more preferably 70% by mass or more, and most preferably 80% by mass or more.
[0030] Examples of polypropylene-based resins include polypropylene homopolymers (propylene homopolymers) and copolymers of propylene and other α-olefins (copolymerizable with propylene). Examples of the "other α-olefins" include α-olefins having 4 to 10 carbon atoms (such as ethylene, 1-butene, isobutylene, 1-pentene, 3-methyl-1-butene, 1-hexene, 3,4-dimethyl-1-butene, 1-heptene, and 3-methyl-1-hexene).
[0031] Propylene homopolymers include linear or branched polypropylenes exhibiting various stereoregularities (isotactic, syndiotactic, atactic, hemiisotactic, etc.).
[0032] The propylene copolymer may be any of a polypropylene random copolymer (random copolymer), a polypropylene block copolymer (block copolymer), a binary copolymer, a ternary copolymer, etc. Specific examples include an ethylene-propylene random copolymer, a butene-1-propylene random copolymer, an ethylene-butene-1-propylene random terpolymer, an ethylene-propylene block copolymer, etc.
[0033] Among the above polypropylene-based resins, a resin containing a polypropylene block polymer is preferred, and a resin made of a polypropylene block polymer is more preferred.
[0034] (1-1-2) Polyethylene resin The polyethylene resin in the present invention includes resins containing ethylene component units in an amount of preferably 50% by mass or more, more preferably 60% by mass or more, even more preferably 70% by mass or more, and most preferably 80% by mass or more.
[0035] Examples of polyethylene resins include high density polyethylene (HDPE), low density polyethylene (LDPE), medium density polyethylene (MDPE), linear low density polyethylene (LLDPE), ethylene-vinyl acetate copolymer, ethylene-propylene copolymer, ethylene-propylene-butene 1 copolymer, ethylene-butene 1 copolymer, ethylene-hexene 1 copolymer, ethylene-4 methylpentene 1 copolymer, and ethylene-octene 1 copolymer.
[0036] The polyethylene-based resin is preferably a resin containing high-density polyethylene and / or linear low-density polyethylene, and more preferably a resin made of high-density polyethylene and / or linear low-density polyethylene.
[0037] The high-density polyethylene preferably has an MFR (190°C, 21.6 kg) according to JIS K 6922-1:2018 (ISO1133) of 5 g / 10 min or more and 15 g / 10 min or less, more preferably 7 g / 10 min or more and 13 g / 10 min or less.
[0038] The linear low-density polyethylene preferably has an MFR (190°C, 2.16 kg) according to JIS K 6922-1:2018 (ISO1133) of 0.5 g / 10 min or more and 1.5 g / 10 min or less, and more preferably has an MFR of 0.7 g / 10 min or more and 1.3 g / 10 min or less.
[0039] In a resin containing high density polyethylene and linear low density polyethylene, the mass ratio of the two (high density polyethylene:linear low density polyethylene) is preferably 90:10 to 50:50, more preferably 92:8 to 50:50, and even more preferably 94:6 to 50:50.
[0040] (1-2) Thermoplastic resin content The content of the thermoplastic resin can be appropriately set depending on the blending amount of the inorganic substance powder, etc.
[0041] From the viewpoint of moldability and the like, the content of the thermoplastic resin is preferably 10% by mass or more, more preferably 15% by mass or more, and even more preferably 20% by mass or more, based on the resin composition.
[0042] The content of the thermoplastic resin is preferably 50% by mass or less, more preferably 45% by mass or less, and even more preferably 40% by mass or less, of the resin composition, from the viewpoint of being able to blend a sufficient amount of inorganic substance powder and easily exhibiting good mechanical properties.
[0043] (2) Inorganic substance powder By blending a predetermined ratio of inorganic powder with a thermoplastic resin, it is possible to suppress variation in mechanical properties of a resin molded product obtained from the resin composition.
[0044] (2-1) Types of inorganic powders The inorganic substance powder is not particularly limited except that it mainly contains calcium carbonate powder, and it is possible to use those contained in ordinary resin molded products, etc. The inorganic substance powder may be one type of substance alone or two or more types of substances in combination.
[0045] (2-1-1) Calcium carbonate powder The calcium carbonate powder may be either heavy calcium carbonate powder or light calcium carbonate powder. "Heavy calcium carbonate" is calcium carbonate obtained by mechanically crushing (dry method, wet method, etc.) natural raw materials whose main component is CaCO3 (limestone, etc.). "Light calcium carbonate" is calcium carbonate prepared by a synthetic method (such as chemical precipitation reaction). Thus, ground calcium carbonate and light calcium carbonate are clearly distinguished from each other.
[0046] The difference between ground calcium carbonate and light calcium carbonate can be identified, for example, from the circularity calculated based on the analysis of SEM images. The roundness of the ground calcium carbonate powder is, for example, in the range of 0.50 to 0.95, and the roundness of the light calcium carbonate powder is, for example, approximately 1.00.
[0047] In one embodiment of the present invention, "circularity" is a value represented by the following formula, and is an index of the degree of irregularity of a particle. The closer the circularity is to "1" (maximum value), the closer it is to a perfect circle, and the lower the value, the higher the degree of irregularity. "Circularity" = (projected area of particle) / (area of circle with the same perimeter as the projected perimeter of the particle)
[0048] Heavy calcium carbonate, due to its manufacturing process, does not have a uniform shape, and is low cost, but it is easy to stably impart good mechanical properties to resin molded products. Therefore, preferred embodiments of the present invention include those in which the calcium carbonate comprises ground calcium carbonate powder, and those in which the calcium carbonate consists of ground calcium carbonate powder.
[0049] (2-1-2) Inorganic powders other than calcium carbonate Examples of inorganic powders other than calcium carbonate include the following: Carbonates, sulfates, silicates, phosphates, or borates of metals (such as titanium, magnesium, aluminum, iron, zinc, etc.); Oxides of metals (titanium, calcium, magnesium, aluminum, iron, zinc, etc.); Hydrates of the above salts or oxides.
[0050] Examples of inorganic substance powders other than calcium carbonate include titanium oxide, magnesium carbonate, zinc oxide, silica, alumina, clay, talc, kaolin, aluminum hydroxide, magnesium hydroxide, aluminum silicate, magnesium silicate, calcium silicate, aluminum sulfate, magnesium sulfate, calcium sulfate, magnesium phosphate, barium sulfate, silica sand, carbon black, zeolite, molybdenum, diatomaceous earth, sericite, shirasu, calcium sulfite, sodium sulfate, potassium titanate, bentonite, and graphite.
[0051] Among the above, from the viewpoint of having a high effect of improving dispersibility and being able to more stably improve the effects of the present invention, it is preferable for the inorganic substance powder other than calcium carbonate to be a component that does not contain any of lead, arsenic, alkali metals, and magnesium as a constituent. Such components are preferably one or more of titanium oxide, zinc oxide, alumina, clay, talc, kaolin, aluminum hydroxide, aluminum silicate, calcium silicate, aluminum sulfate, calcium sulfate, barium sulfate, quartz sand, carbon black, zeolite, molybdenum, diatomaceous earth, sericite, shirasu, calcium sulfite, bentonite, and graphite, and more preferably titanium oxide (TiO2).
[0052] The inorganic powder may be synthetic or derived from natural minerals.
[0053] (2-1-3) When multiple inorganic powders are included In the present invention, when two or more kinds of inorganic substance powders are contained, the combination ratio thereof is not particularly limited except that calcium carbonate powder is contained as a main component, and can be appropriately set depending on the effect to be obtained, etc.
[0054] In one embodiment of the present invention, when two or more types of inorganic substance powders are contained, the combination is preferably a combination containing calcium carbonate and one or more other inorganic substance powders, more preferably a combination containing calcium carbonate and titanium oxide, and even more preferably a combination consisting of calcium carbonate and titanium oxide.
[0055] In one embodiment of the present invention, when calcium carbonate and one or more other inorganic substance powders are contained, the lower limit of the content of the inorganic substance powders other than calcium carbonate is preferably 0.1 mass % or more, more preferably 1 mass % or more, and even more preferably 5 mass % or more, based on the total inorganic substance powders. In one embodiment of the present invention, when calcium carbonate and one or more other inorganic substance powders are contained, the upper limit of the content of the inorganic substance powders other than calcium carbonate is preferably 20 mass % or less, more preferably 10 mass % or less, based on the total inorganic substance powders.
[0056] Whether or not the inorganic substance powder in the resin composition contains calcium carbonate and the amount of calcium carbonate contained therein can be determined by calcining the resin composition and analyzing the ash content. The method for ash analysis can be in accordance with JIS K 7250-1:2006.
[0057] (2-2) Trace components in inorganic powders As described above, the main technical feature of the present invention is that an inorganic substance powder having a content of trace components within a predetermined range is used.
[0058] (2-2-1) Lead In one embodiment of the present invention, the lead content per gram of the inorganic powder is not particularly limited, but may be 19 μg or less. The lower the lead content, the more easily the effects of the present invention are exhibited. The lead content is preferably 10 μg or less, and more preferably 3 μg or less, per gram of the inorganic substance powder. The lower limit of the lead content is not particularly limited, but is preferably 0.0 μg or more per 1 g of the inorganic substance powder.
[0059] Although it is not clear why the variation in mechanical properties can be suppressed by ensuring that the lead content satisfies the above requirements, it is speculated that one factor is that the oxidizing effect of lead on the resin is suppressed while the highly filled inorganic powder stably improves the mechanical properties.
[0060] (2-2-2) Alkali metals and magnesium In one embodiment of the present invention, the total amount of alkali metal and magnesium may be 0.9% by mass or less, when the inorganic substance powder is taken as 100% by mass. The lower the total amount of alkali metals and magnesium, the more easily the effects of the present invention are exhibited. When the inorganic substance powder is taken as 100% by mass, the total amount is preferably 0.8% by mass or less, and more preferably 0.7% by mass or less. The lower limit of the total amount of alkali metal and magnesium is not particularly limited, but is preferably 0.0% by mass or more, assuming that the inorganic substance powder is 100% by mass.
[0061] Although it is not clear why the variation in mechanical properties can be suppressed by ensuring that the alkali metal and magnesium contents satisfy the above requirements, it is speculated that one reason is that the highly filled inorganic substance powder stably improves the mechanical properties while suppressing the deterioration of the resin caused by the oxidation reaction of the alkali metal and magnesium.
[0062] (2-2-3) Other trace elements The contents of the other minor components are not particularly limited, but the higher the purity of the inorganic substance powder, the more easily the effects of the present invention can be achieved.
[0063] For example, when the arsenic content per gram of the inorganic substance powder is preferably 3 μg or less, more preferably 2 μg or less, the safety of the molded article obtained from the resin composition of the present invention is likely to be improved.
[0064] (2-2-4) Method for adjusting the content of trace elements The method for adjusting the contents of trace components is not particularly limited, but examples thereof include the following. Synthesis or collection of inorganic powders that meet the requirements of the present invention. A blend of an inorganic powder not meeting any of the requirements of the present invention with an inorganic powder that does meet the requirements of the present invention. A blend of an inorganic powder that does not meet only one of the requirements of the present invention (e.g., only the lead content) and an inorganic powder that does not meet only another requirement of the present invention (e.g., only the total amount of alkali metal and magnesium).
[0065] (2-2-5) Measurement method for trace elements The amount of trace elements contained in the inorganic powder is specified by the following method described in the 9th edition of the Official Specification of Food Additives (Ministry of Health, Labor and Welfare, Consumer Affairs Agency). The amount of trace elements specified by this method does not necessarily accurately include trace elements contained in the inorganic powder other than calcium carbonate powder in the inorganic powder, but since calcium carbonate powder is the main component in the inorganic powder, it fully reflects the overall properties of the inorganic powder.
[0066] Regarding purity testing of calcium carbonate, the 9th edition of the Food Additives Standards (Ministry of Health, Labour and Welfare, Consumer Affairs Agency) states the following (pages 748-749): (3) Lead: 3 μg / g or less as Pb (2.0 g, Method 5, reference solution: lead standard solution 6.0 mL, flame method) Add 20 mL of hydrochloric acid (1 → 4) to this product, cover with a watch glass, etc., and boil gently for 15 minutes. After cooling, add 30 mL of water to use as the sample solution. If the sample does not dissolve, evaporate to dryness, add 20 mL of hydrochloric acid (1 → 4) to the residue, cover with a watch glass, etc., and boil gently for 5 minutes. After cooling, add 30 mL of water to use as the sample solution. However, change the amount of diammonium hydrogen citrate solution (1 → 2) shown in Method 5 to 50 mL, use 1 mL of bromothymol blue solution as the indicator, and add ammonia water until the solution changes from yellow to yellow-green." (4) Alkali metals and magnesium: 1.0% or less Weigh out 1.0 g of this product, slowly add 30 mL of hydrochloric acid (1 → 10) to dissolve, and boil to expel carbon dioxide. After cooling, neutralize with ammonia TS, add 60 mL of ammonium oxalate monohydrate solution (1 → 25), and heat on a water bath for 1 hour. After cooling, add water to make 100 mL, stir well, filter, measure 50 mL of the filtrate, add 0.5 mL of sulfuric acid, evaporate to dryness, and then ignite at 600°C until constant weight is reached and weigh the mass." (6) Arsenic (As) 3 μg / g or less (0.50 g, standard color arsenic standard solution 3.0 mL, apparatus B) Weigh out this product, moisten it with 1 mL of water, add 4 mL of hydrochloric acid (1 → 4) to dissolve it, and use this as the test solution.
[0067] Regarding purity testing of titanium oxide (titanium dioxide), the 9th edition of the Food Additives Standards (Ministry of Health, Labour and Welfare, Consumer Affairs Agency) contains the following (pages 808-809): (3) Lead: 10 μg / g or less as Pb (4.0 g, reference solution: lead standard solution 4.0 mL, flame method) Add 50 mL of hydrochloric acid (1 → 20) to this product, cover with a watch glass or similar and boil for 20 minutes, then centrifuge to precipitate insoluble matter. Filter the supernatant, wash the container and residue used three times with 10 mL of hot water, and filter using the same filter paper. Furthermore, wash the filter paper used with 10 to 15 mL of hot water and combine the washings with the filtrate. After cooling, add water to make 100 mL and use this as the sample solution. Measure out 10 mL of the sample solution, add 1 / 4 volume of hydrochloric acid, and gently heat to evaporate to dryness. Add a small amount of nitric acid (1 → 100) to the residue and warm. After cooling, add more nitric acid (1 → 100) to make exactly 10 mL, and use this as the test solution. Separately, accurately measure the lead standard solution and add nitric acid (1 → 100) to make exactly 10 mL. Add exactly 10 mL and use this as the comparison solution. (4) Arsenic (As) 1 μg / g or less (10 g, standard color arsenic standard solution 3.0 mL, apparatus B) Weigh out the product, place it in a 250mL beaker, add 50mL of hydrochloric acid (1 → 20), cover with a watch glass or similar and heat until boiling, then gently boil for an additional 15 minutes and centrifuge to precipitate the insoluble matter. Filter the supernatant, wash the beaker and residue three times with 10mL of boiling water each time, and filter using the same filter paper. Furthermore, wash the filter paper used with 10 to 15 mL of boiling water and combine the washings with the filtrate. After cooling, add water to make 100 mL and use this as the sample solution. Measure out 15 mL of the sample solution and use it as the test solution.
[0068] (2-3) Other conditions of inorganic powder The inorganic powder may be in any form so long as it satisfies the above conditions for the minor components.
[0069] The average particle size of the inorganic powder can be appropriately set depending on the moldability of the resin composition to be obtained. However, from the viewpoint of easily achieving stable dispersibility and easily achieving uniform mechanical properties throughout the resin molded product, the average particle size of the inorganic substance powder as measured by the air permeation method in accordance with JIS M-8511:2014 is preferably 0.7 μm or more and 6.0 μm or less, and more preferably 1.0 μm or more and 5.5 μm or less. The average particle size of the inorganic substance powder may be any size as long as the entire inorganic substance powder satisfies the above requirement.
[0070] In order to enhance the dispersibility and reactivity of the inorganic substance powder, the surface of the inorganic substance powder may or may not be previously modified in accordance with a conventional method. Examples of surface modification methods include physical treatment methods (plasma treatment, etc.) and chemical treatment methods (methods using coupling agents or surfactants).
[0071] The shape of the inorganic substance powder is not particularly limited, and may be any of particles (spherical, irregular, etc.), flakes, granules, fibers, and the like.
[0072] (2-4) Amount of inorganic powder The content of the inorganic substance powder is not particularly limited as long as the content of the inorganic substance powder relative to the resin composition is 50% by mass or more and 90% by mass or less.
[0073] From the viewpoint of easily improving mechanical properties, the lower limit of the content of the inorganic substance powder is 50 mass % or more, preferably 52 mass % or more, more preferably 54 mass % or more, and even more preferably 56 mass % or more, relative to the resin composition.
[0074] From the viewpoint of moldability, the upper limit of the content of the inorganic substance powder is 90% by mass or less, preferably 85% by mass or less, more preferably 80% by mass or less, and further preferably 75% by mass or less, based on the resin composition.
[0075] From the viewpoint of easily achieving good mechanical properties, the content of calcium carbonate in the inorganic substance powder is preferably 70 mass % or more, more preferably 80 mass % or more, and most preferably 100 mass % based on the total inorganic substance powder.
[0076] Whether or not the inorganic powder contains calcium carbonate and its content can be determined by firing the resin molded product and analyzing its ash content.
[0077] (3) Other ingredients The resin composition may or may not contain components other than the inorganic substance powder and the thermoplastic resin, as long as the effects of the present invention are not impaired.
[0078] As the other components, any components that can be usually blended in resin molded products can be used. Such components include colorants, lubricants, dispersants, antistatic agents, antioxidants, heat stabilizers, and ultraviolet absorbing agents. The types and amounts of these components can be appropriately determined depending on the effects to be obtained.
[0079] The resin composition in a preferred embodiment of the present invention includes those consisting of only a thermoplastic resin and an inorganic substance powder.
[0080] (4) Ratio of thermoplastic resin to inorganic powder In the resin composition, the mass ratio of the thermoplastic resin to the inorganic substance powder (thermoplastic resin:inorganic substance powder) is preferably 50:50 to 10:90, more preferably 45:55 to 15:85, and even more preferably 40:60 to 20:80. In this way, by making the ratio of the inorganic substance powder to the thermoplastic resin equal to or greater than the above, the effect of improving the mechanical properties by the inorganic substance powder can be easily achieved.
[0081] <Method of producing resin composition> As a method for producing the resin composition, conventionally known methods and conditions can be adopted depending on the form and application of the resin composition.
[0082] The resin composition can be obtained, for example, by mixing, melt-kneading, or the like, the constituent components. The machine for producing the resin composition can be selected depending on the form and application of the resin composition, and examples thereof include an extruder, a kneader, a Banbury mixer, and a kneader (such as a twin-screw kneader).
[0083] The form of the resin composition is not particularly limited, and any form that can be molded into a desired resin molded product (sheet, container, etc.) can be adopted.
[0084] <Resin molded products> The present invention also includes the following resin molded article. A molded article comprising a thermoplastic resin and an inorganic powder, The content of the inorganic powder in the molded article is 50% by mass or more and 90% by mass or less, The thermoplastic resin includes a polyolefin resin, A molded article, wherein the inorganic substance powder mainly contains calcium carbonate powder and satisfies all of the following requirements: (Requirement 1) The lead content per gram of inorganic powder is 19 μg or less. (Requirement 2) When the inorganic substance powder is taken as 100% by mass, the total amount of alkali metals and magnesium is 0.9% by mass or less.
[0085] The details of each component constituting the molded article of the present invention are the same as those of the resin composition of the present invention.
[0086] The molded article of the present invention can be obtained, for example, by molding the resin composition of the present invention by a method appropriate for the type of molded article.
[0087] The molding method for obtaining the molded article of the present invention includes injection molding, extrusion molding, inflation molding, vacuum molding, blow molding, and the like. Therefore, the molded article of the present invention includes any of an injection molded article, an extrusion molded article, an inflation molded article, a vacuum molded article, and a blow molded article. EXAMPLES
[0088] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.
[0089] <Preparation and evaluation of resin composition> A resin composition was prepared by the following method, and a molded article obtained from the resin composition was evaluated for variation in mechanical properties.
[0090] (1) Preparation of materials The materials for each layer were prepared as follows:
[0091] (1-1) Inorganic substance powder The following inorganic powders were prepared: Calcium carbonate particles (heavy calcium carbonate particles): The average particle size of the calcium carbonate particles was 2.0 μm, measured using an air permeability method in accordance with JIS M-8511:2014. Titanium oxide particles: The average particle size of the titanium oxide particles was 0.6 μm, as measured by the air permeability method in accordance with JIS M-8511:2014.
[0092] The following "Inorganic Powder 1" to "Inorganic Powder 6" were prepared using only calcium carbonate particles. First, three types of calcium carbonate with different trace element contents (calcium carbonate purity) collected from different mines were blended in various ratios to prepare "Inorganic Powder 1" to "Inorganic Powder 6." These "Inorganic Powder 1" to "Inorganic Powder 6" were used in the amounts shown in Table 1. The trace element contents in calcium carbonate particles were measured in accordance with the section on "Calcium Carbonate" (pages 748-749) of the 9th edition of the Official Specification of Food Additives (Ministry of Health, Labor and Welfare, Consumer Affairs Agency). This official specification specifies the method for measuring trace elements (lead, alkali metals and magnesium, hydrochloric acid insoluble matter, free alkali, etc.) contained in calcium carbonate.
[0093] Furthermore, the following "Inorganic Powder 7" was prepared using calcium carbonate particles and titanium oxide particles. The purchased titanium oxide particles and calcium carbonate particles were blended in a mass ratio of titanium oxide particles:calcium carbonate particles of 10:90 to prepare "Inorganic Powder 7." As the calcium carbonate particles, "Inorganic Powder 1" was used. The trace element content in the titanium dioxide particles was measured in advance in accordance with the section on "calcium carbonate" (pages 748-749) of the 9th edition of the Official Specification for Food Additives (Ministry of Health, Labor and Welfare, Consumer Affairs Agency), and all trace elements contained in the titanium dioxide were below the detection limit. Therefore, the amount of trace elements contained in the inorganic substance powder used in this example is consistent with the amount of trace elements contained in the calcium carbonate powder.
[0094] In Table 1, the contents of each trace component have the following meanings. Lead: Lead content per gram of inorganic powder (unit: μg) Alkali metals: The total amount of alkali metals and magnesium when the inorganic powder is taken as 100% by mass (unit: mass%) Arsenic: Arsenic content per gram of inorganic powder (unit: μg)
[0095] [Table 1]
[0096] (1-2)Thermoplastic resin Any of the following thermoplastic resins (all of which correspond to polyolefin-based resins) was used. Polypropylene resin (PP): Polypropylene block copolymer (melting point 160°C) Polyethylene resin (PE): Blend of HDPE and LLDPE (HDPE:LLDPE (mass ratio) = 70:30) The MFR (190°C, 21.6 kg) of the above HDPE according to JIS K 6922-1:2018 (ISO1133) is 7.5 g / 10 min. The MFR (190°C, 2.16 kg) of the above LLDPE according to JIS K 6922-1:2018 (ISO1133) is 0.8 g / 10 min.
[0097] (2) Preparation of resin composition and molded product A thermoplastic resin (PP or PE) and an inorganic substance powder were melt-kneaded in the ratios shown in Tables 2 and 3, and then a pellet-shaped resin composition was obtained. Next, the obtained resin composition was injection molded into a plate-shaped molded product (length 80 mm × width 10 mm × thickness 4 mm).
[0098] (3) Heat degradation test Each molded article was subjected to heat aging treatment in accordance with JIS K7368:1999. The conditions for the heat aging treatment were as follows. The temperature conditions were all set to a value not exceeding the melting point of the resin. When the polyolefin resin is a polypropylene resin: 150°C, 168 hours When the polyolefin resin is a polyethylene resin: 121°C, 168 hours
[0099] (4) Tensile test After the heat degradation test was completed, each molded product (600 pieces for each test group) was subjected to a tensile test using an autograph AG-100kNXplus (Shimadzu Corporation) under conditions of 23°C, 50% RH, and an extension speed of 50 mm / min in accordance with JIS K7161-1:2014 to measure the tensile strength.
[0100] The tensile strength of the molded products in each test group was evaluated according to the following criteria. The results are shown in Tables 2 and 3. A: The standard deviation of the tensile strength was less than 5%. B: The standard deviation of the tensile strength was 5% or more but less than 10%. C: The standard deviation of the tensile strength was 10% or more but less than 15%. D: The standard deviation of the tensile strength was 15% or more.
[0101] [Table 2]
[0102] [Table 3]
[0103] As shown in the table, the resin composition satisfying the requirements of the present invention gave molded articles in which the variation in mechanical properties (tensile strength in this example) was suppressed even after being subjected to heat degradation treatment. Furthermore, although no data is shown, all of the molded articles obtained from the resin compositions satisfying the requirements of the present invention had tensile strength sufficient for practical use in various applications such as containers.
[0104] In contrast, when the inorganic powder did not satisfy the requirements of the present invention, the mechanical properties varied. When only "Inorganic Powder 3" or "Inorganic Powder 6" was used as the inorganic powder, the effect of the present invention was not obtained, but when "Inorganic Powder 3" and "Inorganic Powder 6" were blended and the inorganic powder was adjusted to satisfy the requirements of the present invention, the same results as those of the examples were obtained.
[0105] The same tendency as above was obtained when other inorganic powders (titanium oxide in this example) were used as the inorganic powder together with the heavy calcium carbonate powder. Furthermore, in the same manner as with "Inorganic Powder 7," "Inorganic Powder 2" to "Inorganic Powder 6" were also blended in a titanium oxide particle:calcium carbonate particle (mass ratio) of 10:90, and the same tendencies were observed as when only "Inorganic Powder 2" to "Inorganic Powder 6" were used, respectively. This indicates that, so long as the inorganic powder is used in a manner that satisfies the requirements of the present invention, the type of inorganic powder itself does not have a significant effect on the results.
[0106] In this example, heavy calcium carbonate powder was used as the inorganic powder, but the same tendency as above was observed with other inorganic powders (light calcium carbonate powder, talc powder, etc.).
[0107] In this example, injection molding was used as the molding method for the resin composition, but the same tendency as above was observed even in the case of molded products formed by other molding methods.
Claims
1. A resin composition comprising a thermoplastic resin and an inorganic substance powder, The content of the inorganic substance powder in the resin composition is 50% by mass or more and 90% by mass or less, the thermoplastic resin includes a polyolefin resin, A resin composition, wherein the inorganic substance powder mainly contains calcium carbonate powder and satisfies all of the following requirements: (Requirement 1) The lead content per gram of the inorganic substance powder is 19 μg or less. (Requirement 2) When the inorganic substance powder is taken as 100% by mass, the total amount of alkali metal and magnesium is 0.9% by mass or less.
2. The resin composition according to claim 1 , wherein the polyolefin-based resin comprises a polypropylene-based resin and / or a polyethylene-based resin.
3. The resin composition according to claim 1 , wherein the content of the calcium carbonate powder is 80 mass % or more relative to the inorganic substance powder.
4. The resin composition according to claim 1 , wherein the calcium carbonate powder comprises ground calcium carbonate powder.
5. The resin composition according to claim 1 , wherein the inorganic powder further satisfies the following requirements: (Requirement 3) The arsenic content per gram of the inorganic substance powder is 3 μg or less.
6. The resin composition according to claim 4, wherein the heavy calcium carbonate powder contains heavy calcium carbonate powder having an average particle size of 0.7 μm or more and 6.0 μm or less as measured by an air permeation method in accordance with JIS M-8511:2014.
7. A molded article comprising a thermoplastic resin and an inorganic powder, The content of the inorganic substance powder in the molded article is 50% by mass or more and 90% by mass or less, the thermoplastic resin includes a polyolefin resin, The inorganic substance powder mainly contains calcium carbonate powder, and the molded article satisfies all of the following requirements: (Requirement 1) The lead content per gram of the inorganic substance powder is 19 μg or less. (Requirement 2) When the inorganic substance powder is taken as 100% by mass, the total amount of alkali metal and magnesium is 0.9% by mass or less.
8. The molded article according to claim 7 , wherein the molded article is any one of an injection molded article, an extrusion molded article, an inflation molded article, a vacuum molded article, and a blow molded article.
Citation Information
Patent Citations
Thermoplastic resin composition containing inorganic substance powder and compact
JP2020158560A